Availability of individual proteins for quantitative analysis in postmortem brains preserved in two different brain banks - Atsuko Nagaoka; Mizuki Hino; Ryuta Izumi; Risa Shishido; Miki Ishibashi; Masataka Hatano; Makoto Sainouchi; Akiyoshi Kakita; Hiroaki Tomita; Yasuto Kunii (Wiley, 2024)
Abstract Aim Postmortem brain research is necessary for elucidating the pathology of schizophrenia; an increasing number of studies require a combination of suitable tissue samples preserved at multiple brain banks. In this study, we examined whether a comparative study of protein expression levels can be conducted using postmortem brain samples preserved in different facilities. Methods We compared the demographic factors of postmortem brain samples preserved in two institutions and measured and compared the expression levels of glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) and glial fibrillary acidic protein (GFAP) in the prefrontal cortex and superior temporal gyrus. GAPDH is generally used as a loading control for western blotting, and GFAP is considered as an astrocyte marker in the brain. Results We found significant differences between the two institutions in postmortem interval, age at death, and preservation time. To reduce the effects of these differences on our measurements, the parameters were set as covariates in our analyses of covariance. Subsequently, no differences in GAPDH and GFAP expression were found between institutions. Conclusions When studies are conducted using brain samples preserved in different brain banks, differences in demographic factors should be carefully considered and taken into account by statistical methods to minimize their impact as much as possible. Since there was no significant difference in the protein expression levels of GAPDH and GFAP in either region between the two institutions that preserved the postmortem brains, we concluded that it is possible to perform protein quantitative analysis assuming that there is no effect of difference between two institutions.